People participating in the 1986 y-Walk - Unknown:::Creator::::::::::::
Negative shows a group of men and women participating in the 1986 y-Walk. They are walking down a sidewalk in what appears to be a downtown area. There is a piece of a brick building visible on the left side of the photograph and on the street is a semi-truck with dry wall on its bed and a few parked vehicles. Some of the women are wearing tee shirts that read: "Walk for women. YWCA 1986" and some are carrying balloons.